Analyzing the Relationship between Interval-valued D-Implications and Interval-valued QL-Implications - Reiser, R.H.S.; Bedregal, B.R.C; Santiago, R.H.N; Dimuro, G.P. (Trends in Computational and Applied Mathematics, 2010)
The aim of this work is to analyze the relationship between interval QLimplications and their contrapositions named interval D-implications. In order to achieve this aim, the commutative classes relating to these concepts are studied. We also analyze under which conditions the main properties corresponding to punctual D-implications and QL-implications are still valid when an interval-based fuzzy approach, on the best interval representation, is considered.